URGENSI KEPEMIMPINAN TRANSFORMASIONAL: MENUMBUHKAN BUDAYA INOVASI DALAM LEMBAGA DAKWAH DI ERA DIGITAL - Sabirin, Yoga Basyiril; Castrawijaya, Cecep (JURNAL MANAJEMEN DAKWAH, 2025)
Social change and rapid technological development require da'wah institutions to adapt to remain relevant and effective in spreading religious messages. This research aims to explore the relevance of transformational leadership and culture of innovation in da'wah institutions in the digital era. The method used is a qualitative approach with a literature study, which involves analyzing literature on transformational leadership and innovation in the context of da'wah. The results showed that transformational leadership plays an important role in inspiring and motivating members of da'wah institutions to adapt to changing times. Visionary and innovative leaders are able to create a dynamic ecosystem, directing da'wah institutions to utilize digital technology and social media in spreading religious messages to a wider audience, especially the younger generation. The culture of innovation implemented in da'wah institutions allows for the creation of creative solutions that respond to the challenges of the times, such as the use of da'wah applications or digital platforms to increase the reach and relevance of da'wah. However, the main challenges in implementing transformational leadership are resistance to change from conservative members and limited resources. Dawah leaders must have good communication skills to convince members that innovations remain grounded in religious principles. This study concludes that transformational leadership and a culture of innovation are essential to improving da'wah effectiveness in the digital era, despite the challenges that must be overcome through adaptive and creative approaches.